Decadal trajectories of phytoplankton communities in contrasted estuarine systems in an epicontinental sea. (5th September 2021) - Lefran, Angéline; Hernández-Fariñas, Tania; Gohin, Francis; Claquin, Pascal
Abstract: In coastal areas, global changes are known to affect estuaries and their plume leading to water temperature increase and river discharge variations, which are two of the main drivers controlling phytoplankton dynamics. This paper aims at understanding the past 10 years' variations in term of communities' stability and trajectories along with their relationship with the environment. Considering the high environmental variability along coastal areas, we focused our study on six contrasted estuarine systems from the eastern English Channel. Using monthly monitoring from 2008 to 2019, the response of the micro-phytoplankton compartment was investigated through the abundances of a hundred taxa and several abiotic parameters' records. The results indicate an overall stability in community composition with an average of 30–40% similarity between pairs of samples over the study period. The phytoplankton assemblages also display greater spatial heterogeneity during summer in comparison with other seasons. The co-inertia analysis highlighted four separate systems linked to major drivers; a system under strong river and nutrient flows influence, a well-mixed and oxygenized estuary, a system challenged by offshore marine waters, and finally a system under shellfish farms pressure. This structuration is built from the dominance of a handful of species that differs from one place to another, which explains why phytoplankton is mostly site specific. Additionally, the low variations led a by few species' dominance also explains the inter-annual stability noticed during summer at each area, in spite of the high diversity observed. Highlights: Decadal stability was found in phytoplankton communities in several estuarine systems. Average of 30–40% of similarity observed between pair of samples over the decadal period. Co-inertia analysis highlighted four separate systems according to their major drivers. Community Trajectory Analysis show greater spatial heterogeneity during summer. The dominance of few species explains phytoplankton's estuarine site's specificity.